Establishing Dosing Recommendations for Efavirenz in HIV/TB-Coinfected Children Younger Than 3 Years. (1st August 2019) - Bwakura Dangarembizi, Mutsa; Samson, Pearl; Capparelli, Edmund V.; Moore, Carolyn Bolton; Jean-Philippe, Patrick; Spector, Stephen A.; Chakhtoura, Nahida; Benns, Alex; Zimmer, Bonnie; Purdue, Lynette; Jackson, Chivon; Wallis, Carole; et al.
Abstract : Background: CYP2B6 516 genotype-directed dosing improves efavirenz (EFV) exposures in HIV-infected children younger than 36 months, but such data are lacking in those with tuberculosis (TB) coinfection. Methods: Phase I, 24-week safety and pharmacokinetic (PK) study of EFV in HIV-infected children aged 3 to <36 months, with or without TB. CYP2B6 516 genotype classified children into extensive metabolizers (516 TT/GT) and poor metabolizers [(PMs), 516 TT]. EFV doses were 25%–33% higher in children with HIV/TB coinfection targeting EFV area under the curve (AUC) 35–180 μg × h/mL, with individual dose adjustment as necessary. Safety and virologic evaluations were performed every 4–8 weeks. Results: Fourteen children from 2 African countries and India with HIV/TB enrolled, with 11 aged 3 to <24 months and 3 aged 24–36 months, 12 extensive metabolizers and 2 PMs. Median (Q1, Q3) EFV AUC was 92.87 (40.95, 160.81) μg × h/mL in 8/9 evaluable children aged 3 to <24 months and 319.05 (172.56, 360.48) μg × h/mL in children aged 24–36 months. AUC targets were met in 6/8 and 2/5 of the younger and older age groups, respectively. EFV clearance was reduced in PM's and older children. Pharmacokinetic modeling predicted adequate EFV concentrations if children younger than 24 months received TB-uninfected dosing. All 9 completing 24 weeks achieved viral suppression. Five/14 discontinued treatment early: 1 neutropenia, 3 nonadherence, and 1 with excessive EFV AUC. Conclusions: Genotype-directed dosing safely achieved therapeutic EFV concentrations and virologic suppression in HIV/TB-coinfected children younger than 24 months, but further study is needed to confirm appropriate dosing in those aged 24–36 months. This approach is most important for young children and currently a critical unmet need in TB-endemic countries. Abstract : Supplemental Digital Content is Available in the Text.